1988
DOI: 10.4141/cjas88-003
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Hormonal Interrelationships in Beef Cattle Reproduction

Abstract: Reproductive rate has a major influence on production efficiency of beef cattle, and nutritional management is the main limiting or controlling factor for reproduction. Decreased availability of energy is the most common problem studied in beef cattle management and will be the primary focus of this review. In order to effectively manage energy nutrition, we need a better understanding of how this variable affects the various phases and control mechanisms of reproduction. Insufficient energy intake because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 16 publications
(19 reference statements)
2
75
0
2
Order By: Relevance
“…A característica produtiva mais sensível de uma vaca em reprodução é a taxa de reconcepção, pois é a última a receber energia disponível, que segue a seguinte ordem de importância: metabolismo basal, atividade, crescimento, reservas de energia, prenhez, lactação, reservas adicionais de energia, ciclo estral e início de prenhez e reservas de energia em excesso (Short & Adams, 1988). Como no período pré-parto (60-90 dias antes da parição) as exigências energéticas das vacas de corte ainda são baixas, esse é o período mais adequado para adotar estratégias de manejo nutricional, pois nesta fase as vacas podem armazenar gordura de forma mais rápida e econômica.…”
Section: Resultsunclassified
“…A característica produtiva mais sensível de uma vaca em reprodução é a taxa de reconcepção, pois é a última a receber energia disponível, que segue a seguinte ordem de importância: metabolismo basal, atividade, crescimento, reservas de energia, prenhez, lactação, reservas adicionais de energia, ciclo estral e início de prenhez e reservas de energia em excesso (Short & Adams, 1988). Como no período pré-parto (60-90 dias antes da parição) as exigências energéticas das vacas de corte ainda são baixas, esse é o período mais adequado para adotar estratégias de manejo nutricional, pois nesta fase as vacas podem armazenar gordura de forma mais rápida e econômica.…”
Section: Resultsunclassified
“…Joubert 1954;Durrell 1955;Wiltbank et al 1962;Richards et al 1986;Louw et al 1988). Food energy tends to be prioritised for survival rather than reproductive functions, the order of priority from greatest to lowest being: 1) basal metabolism, 2) activity, 3) growth, 4) basic energy reserves, 5) pregnancy, 6) lactation, 7) additional energy reserves, 8) oestrous cycles and initiation of pregnancy and 9) excess reserves (Short and Adams 1988). Thus, when food becomes limited, the oestrous cycle will be one of the first physiological functions to become inactive (ibid.…”
Section: Manipulation Of Calving Seasonalitymentioning
confidence: 99%
“…All ewes that manifested estrus during the breeding season were fertilized, according to the fertility rates (Table 6), verified by the lack of repetition of heat after mounting. The reproductive response of the ewes subjected to flushing and pre-mating shearing was possibly related to their higher nutrient intake, because feeding quantitatively and qualitatively inappropriate diets is among the main causes of prolonged anestrus (SHORT;ADAMS, 1988). This result agrees with those reported by Leal et al (2010), who evaluated the reproductive performance of Santa Inês ewes receiving dietary supplementation and found a rapid return to estrus; by Sabra and Hassan (2008), who found an extension of estrus in animals when studying the reproductive performance of Barki ewes subjected to flushing; and by Islam et al (2007), who reported an improvement in the reproductive efficiency of Corriedale ewes also subjected to flushing.…”
Section: Resultsmentioning
confidence: 99%